An Error Analysis In Writing Descriptive Text Made By 8th Grade Students Of Smp Al-Islam Kartasura In 2013/2014 Academic Year - , Effendy, Dr. Dwi Haryanti, M.Hum, Drs. Sigit Haryanto, M.Hum (2014)
This study aims atdescribing the learners' error made by eight grade students of SMP AL-Islam Kartasura in their composition of writing descriptive text: Identify the types of lexical errors, syntactical errors, and discourse errors; classification the frequency of each type of errors; describes the dominant type of errors; and identifying the source of errors. The type of this research is descriptive qualitative research. In collecting the data the writer uses elicitation technique. There are six steps to collect data, namely: the writer enters the class, the writer asked the students to write descriptive text, the writer read the composition made by students accurately, the writer marked the erroneous sentences, then the writer listed the erroneous sentence and classifies the data into all types of error. In analyzing the data, the writer uses James theory for classification of errors, Slamet theory for the frequency of each type of error and Brown, Norish, Richard for sources of errors theory. The result of the research shows that eight grade students of SMP AL Islam Kartasura still made 137 errors in their compositions.There are three classifications of error based on the combination of linguistic category taxonomy and surface strategy taxonomy. Lexical Errorsconsists 55, 47% that cover wrong spelling 44, 52%, false friend (similar in form) 0, 72%, and 'use Indonesian word/code switching' 10, 21%.Syntactical Errors consists of 40, 14% covers pronoun from subjective for possessive adjective3, 64%, pronoun from subjective for objective5, 10%, Be from addition of BE in Subject4, 37%, BE from omission of BE in Subject 2, 18%, BE from omission of BE as Predicate5, 10%, Plural from omission of (-S) as plural marker14, 59%, The use of verb tense from misuse of have4, 37%, The use of verb tense from misuse of has0, 72% of errors).Errors on discourse are made up of 4, 37%. The error classified into one error, namely: discourse error from conjunction4, 37%. The researcher also finds 2 dominant sources of error, namely interlingual transfer and intralingual transfer. So, the eighth grade students in SMP Al- Islam Kartasuraespecially in class C still made errors in their composition in writing descriptive text. The dominant error is lexical error especially in wrong spelling.